Kierkegaard: The Self in Society - Shakespeare, Steven. author. aut Link
XII, 225 p.
Keywords: Kierkegaard: The Self in Society brings together scholars from a variety of disciplines to explore Kierkegaard's continuing relevance to political and social issues. Kierkegaard is often portrayed as an out-and-out individualist with no concern for interpersonal relations. These essays not only refute this caricature, they bring out the complex nature of Kierkegaard's engagements with questions of selfhood and society. What Kierkegaard has to say about love, the church, politics and justice is shown to test the limits of what we take for granted in the modern (and postmodern) world.